Agricultural market regulations and their impact on marketing of paddy, jute and mustard in Assam, India - Bhuyan, Sanjib; Weber, Karl E.; Demaine, Harvey; Amin, A.T.M. Nurul; Routray, Jayant Kumar; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1988)
The concept of market regulation for agricultural produce in India is unique in that it tries to link marketing of agricultural produce to economic development of the rural masses. The exclusive objective of market regulations is to protect the interest of the producer-sellers from traditional and malign market operations, and to bring about an efficient marketing system throughout the country through establishment and operationalization of regulated markets . Even a century after the inception of market regulations the question still remains in how far they are effective in bringing about an efficient marketing system for agricultural produce, and whether producer-sellers are benefited at all. The major objective of this study, thus, is to determine how these market regulations were operationalized in Assam where the advent of regulation is comparatively new, and whether marketing of agricultural produce is to the benefit of producer-sellers. The study had to be conducted in conventional markets within regulated market areas as the regulated market yards were not functioning. Target groups were producer-sellers (PS) and market functionaries (MF). Conventional markets operating near the regulated market yards and l ack of coordination among Government departments were the reasons for the non-functioning of regulated market yards. Analysis of the market structure of these conventional markets showed that these markets were oligopolistic by nature, and producer sellers were at the mercy of the buyers although market regulations had been in effect since 1977. Marketing channels with least number of intermediaries were found most efficient for selected crops. Major cost items for PS were market charge, deduction and transportation, while, for MF transportation, cess and taxes formed the major cost items. Seasonality in prices was pronounced in all markets. Among selected crops mustard showed relatively higher variolations in price . A qualitative analysis of target groups showed that conventional markets were able to fulfil the need of the people. Lack of knowledge about market regulations and locational shortcomings of the Principal Market Yards prevented PS from attending there. Market Committee had failed to close the communication gap between itself and the target population. Recommendations for planning include alternative strategies for market regulations and regulated markets , integrated marketing strategies for the producer-sellers and suggestions for improvement of the existing marketing system.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Farm produce -- India -- Marketing